Studying of Laser Tissue Interaction Using Biomedical Tissue - Salman, Ansam M.; Jaffar, Amal F.; Al-Taie, Alaa Ayyed Jebur (Al-Nahrain Journal for Engineering Sciences, 2017)
In our work, three internal regions of rat are exposed to four different lasers with different power density, and then studying the histology of the tissues. Together the total absorption and transmission of the tissues at certain wavelength were determined.Changing the wavelength across the absorption peak caused a significant difference in laser tissue interactions and changing the absorption coefficient, relaxation time, generated heat, and the intensity as a function of penetration depth. Furthermore, little mechanical damage could be seen in conventional histology.